The 100 Rules of Brasilia as a tool to address barriers to access to justice: the gender approach as a factor of vulnerability - Timaná Álvarez, Melina (2023)
This article will address the special difficulties faced by people in conditions of vulnerability in relation to the full enjoyment of theright to access to justice, giving a special look at the gender approach as a vulnerability factor. Likewise, an overview is made of how the way of interpreting and understanding our legal system has evolved in those cases in which there is a gender perspective on the part of judicial officials, as well as legal operators in general as a result of the approval of the 100 Rules of Brasilia.